2014
DOI: 10.1111/1471-0307.12154
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐obesity effect of feeding probiotic dahi containing Lactobacillus casei NCDC 19 in high fat diet‐induced obese mice

Abstract: Nowadays, studies about the anti‐obesity potential of probiotics are of growing interest. Lactobacilli are one of the well‐studied probiotics owing to their preventing effect on metabolic disorders. This study was undertaken to access the anti‐obesity effect of probiotic dahi containing Lactobacillus casei NCDC 19 on C57BL/6 mice. Feeding of probiotic dahi showed reduce body weight gain and epididymal fat weights. Moreover, blood glucose, plasma lipids and expression level of leptin were reduced and caecal bif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…The administration of T17, however, significantly alleviated insulin resistance and decreased the serum levels of TG, T-CHO and LDL-C in HFD-fed mice, which may be partly explained by the significant increase in adiponectin, assumedly due to the reduction in adipocyte size in accordance with previous studies [31]. Adiponectin is known to play an important role in regulating energy homeostasis, and the improvement in adiponectin as a result of T17 feeding may be linked to the regulation of lipid metabolism, leading to a balanced serum lipid profile [32]. Another hormone synthesized and secreted by adipose tissue, leptin, is produced in proportion to fat stores and exerts negative feedback effects on energy intake to permit energy expenditure.…”
Section: Discussionsupporting
confidence: 86%
“…The administration of T17, however, significantly alleviated insulin resistance and decreased the serum levels of TG, T-CHO and LDL-C in HFD-fed mice, which may be partly explained by the significant increase in adiponectin, assumedly due to the reduction in adipocyte size in accordance with previous studies [31]. Adiponectin is known to play an important role in regulating energy homeostasis, and the improvement in adiponectin as a result of T17 feeding may be linked to the regulation of lipid metabolism, leading to a balanced serum lipid profile [32]. Another hormone synthesized and secreted by adipose tissue, leptin, is produced in proportion to fat stores and exerts negative feedback effects on energy intake to permit energy expenditure.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, a recent study revealed that the abundance of A. muciniphila decreased in HFD-fed mice, which is strongly correlated with weight gain, increased inflammation, increased expression of lipid-metabolism genes in adipose tissues, and increased level of blood markers (e.g., lipid and glucose) in obese mice (Schneeberger et al, 2015). Accumulating evidence shows that probiotic administration leads to a reduction in body weight gain, adipose weight, and obesity biomarkers (e.g., glucose and plasma lipid) in HFD-fed mice (Rather et al, 2014; Parker et al, 2017). In addition, the effect of probiotics on the improvement of metabolism was confirmed in normal mice (Zhao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that feeding of probiotic dahi, which contains L. casei NCDC 19, led to a reduction in epididymal fat weights, blood glucose, plasma lipids, leptin levels, and body weight among HFD mice (Rather et al, 2014). These observed effects were correlated with an increase in the population of bifidobacteria .…”
Section: Modulation Of Gut Microbiota By Dietary Approaches For Theramentioning
confidence: 99%